Green BPM – the essence, premises for introduction and its challenges - Brajer-Marczak, Renata (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
To meet the contemporary needs related to limiting the negative impact of the organization on the natural environment, the concept of Green Business Process Management (Green BPM) has been developed. Thereby, the concept of Green Business Process Management (Green BPM) began to gain importance. The aim of the study is to characterize this concept, as well as to indicate the premises for its introduction and problems accompanying it in relation to the challenges of creating socially and environmentally responsible organizations. To achieve this goal, the author relied on the critical analysis of the literature on the subject, the query of internet sources and secondary empirical data analysis. As a result of the analysis, it was found that orientation of process management towards care for the natural environment is a big challenge, requiring technological changes, but also covering the cultural and social dimensions of the organization. In practice, the implementation of the Green BPM concept is associated more often with the use of single pro-environmental solutions than with overall changes in BPM.